1991
DOI: 10.1200/jco.1991.9.10.1749
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of early relapse in patients with operable breast cancer by detection of occult bone marrow micrometastases.

Abstract: We used monoclonal antibodies to identify occult micrometastases in the bone marrow of 49 patients with operable (stage I and II) breast carcinoma. Follow-up (mean, 29 months; median, 30 months) revealed that 12 patients recurred. The presence of bone marrow micrometastases (BMM) was significantly associated with early recurrence (P less than .04). The estimated 2-year recurrence rate for patients with no BMM detected (BMM-) was 3%; in patients with BMM, the 2-year recurrence rate was 33%. When BMM and axillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
165
1
8

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(179 citation statements)
references
References 23 publications
5
165
1
8
Order By: Relevance
“…We shall be examining the associations of such factors in these patients in the near future. Detection of metastatic tumour cells in bone marrow of breast cancer patients is now also feasible and may have prognostic significance (Cote et al, 1991;Dearnaley et al, 1991), and could also be combined into a risk index.…”
Section: Discussionmentioning
confidence: 99%
“…We shall be examining the associations of such factors in these patients in the near future. Detection of metastatic tumour cells in bone marrow of breast cancer patients is now also feasible and may have prognostic significance (Cote et al, 1991;Dearnaley et al, 1991), and could also be combined into a risk index.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in the setting of autologous bone marrow transplantation (ABMT) or peripheral stem cell reinfusion after high-dose chemotherapy, contamination of the reinfused bone marrow or stem cell population with tumour cells might worsen prognosis (Anderson et al, 1989;Gribben et al, 1991;Brenner et al, 1993;Brugger et al, 1994;Moss et al, 1994). In recent years, especially in breast and colon cancer, it has been shown that occult contamination of the peripheral blood or bone marrow at diagnosis with tumour cells exerts an adverse influence on survival (Berger et al, 1988;Cote et al, 1991;Schlimok et al, 1991;Pantel et al, 1993;Diel et al, 1994;Harbeck et al, 1994;Menard et al, 1994). Often, in these studies, a monoclonal antibody (MAb) or a panel of MAbs directed against tumour cell-surface glycoproteins or cytokeratins was used to detect circulating tumour cells.…”
mentioning
confidence: 99%
“…19,20 Keywords: bone marrow; transplantation; breast cancer Given these considerations, we designed a treatment strategy for patients with metastatic breast cancer consisting of high-dose alkylating agent chemotherapy followed by with the goal of eradicating small numbers of malignant period, on days −10 to day −1. Four patients received posttransplant radiation to areas of persistent abnormalities on cells that may have been unknowingly reinfused with the autograft.…”
Section: Eight (24%) Achieved Partial Response (Pr) 12 (35%)mentioning
confidence: 99%